Function of Dicer with regard to Energy Homeostasis Regulation, Structural Modification, and Cellular Distribution - Xiaohui Tong; Nianjun Yu; Rongchun Han; Tongsheng Wang (International Journal of Endocrinology)
As a type III ribonuclease (RNase III) specifically cleaving double-stranded RNA substrates into short fragments, Dicer is indispensable in a range of physi/pathologic processes, e.g., nutrient deprivation, hypoxia, or DNA damage. Therefore, much interest has been paid to the research of this protein as well as its products like microRNAs (miRNAs). The close relationship between Dicer levels and fluctuations of nutrient availability suggests that the protein participates in the regulation of systemic energy homeostasis. Through miRNAs, Dicer regulates the hypothalamic melanocortin-4 system and central autophagy promoting energy expenditure. Moreover, by influencing canonical energy sensors like adenosine monophosphate-activated protein kinase (AMPK) or mammalian target of rapamycin (mTOR), Dicer favors catabolism in the periphery. Taken together, Dicer might be targeted in the control of energy dysregulation. However, factors affecting its RNase activity should be noted. Firstly, modulation of structural integrity affects its role as a ribonuclease. Secondly, although previously known as a cytosolic endoribonuclease, evidence suggests Dicer can relocalize into the nucleus where it could also produce small RNAs. In this review, we probe into involvement of Dicer in energy homeostasis as well as its structural integrity or cellular distribution which affects its ability to produce miRNAs, in the hope of providing novel insights into its mechanism of action for future application.